The association between neurocognition and sexual abuse within a children's psychiatric inpatient program. Issue 1 (2nd January 2022) - Gervasio, Maddi; Beatty, Avery; Kavanaugh, Brian; Cancilliere, Mary Kathryn; Holler, Karen
Abstract: Objective : The aim of this study was to understand the detrimental effects of sexual abuse on neuropsychological variables including child's intelligence, executive functioning (EF), and learning/memory within a pediatric inpatient population. Method : This study examined the effect of sexual abuse on children's intelligence, EF, and learning/memory by conducting a retrospective chart review for 144 children (aged 7-12) who completed a neuropsychological assessment during a psychiatric inpatient hospitalization. Of the 144 children, participants were matched two to one by gender and age, with one group (n = 52) categorized by reported sexual abuse and the other group (n = 92) categorized by no reported sexual abuse. The neuropsychological measures included the Wechsler Abbreviated Scale of Intelligence (WASI-I/II) or Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV), Wide Range Assessment of Memory and Learning – Second Edition (WRAML-2): Story Memory Immediate/Delayed Recall and Delayed Recognition, Trail Making Test-B, Stroop Interference Test: Color-Word Condition, WRAML-2: Sentence Memory and Conners Continuous Performance Test-Second Edition. Results : Statistical analysis showed that participants with reported sexual abuse had significantly (p< .05) lower intelligence, EF, and learning/memory skills than those without reported sexual abuse. Only working memory and cognitive flexibility differences remained after controlling for clinical variables (e.g., PTSD, amount of total abuse types). Conclusions : These findings contributed to the limited research on the detrimental effects of sexual abuse in a pediatric inpatient population. They demonstrated a relationship between early sexual abuse and neuropsychological deficits, specifically executive function and IQ deficits.